THE TERM OF MIGRATION AND ITS MAIN SCIENTIFIC-THEORETICAL MEANINGS - Marguba Makhsudovna Nosirova (Galaxy International Interdisciplinary Research Journal, 2022)
In this article has been analyzed disciplines study population migration as a special process, but often population migration is included in the perspective of sociology, economics, demography, geography and history as well.